Bhutan Development Update, June 2018 : Youth Unemployment Rate Increased under High Growth - World Bank Group (World Bank, Washington, DC, 2018)
Bhutan maintained solid growth and macroeconomic stability during 2016/17. The national poverty headcount rate fell from 12 percent in 2012 to 8 percent in 2017. However, the job challenges remained unaddressed. the youth unemployment rate increased from 10.7 percent in 2015 to 13.2 percent in 2016 indicating that high growth was not able to generate enough jobs for youth.